PEMANFAATAN TEKNOLOGI PELAPIS HPL SPRING FLEXIBLE GUNA MENINGKATKAN PRODUKTIVITAS FURNITUR CV CID - Abdul Hadi, Afif; Kusumawardana, Arya; Afnan Habibi, Muhammad; Abdi Mahadiraja, Fajar; Tifandi Satriani, Cahya; Pablo Octavianus, Juan; Faiz Risvan Haqiqi, Ahmad (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
This program focuses on the design and implementation of a High Pressure Laminate (HPL) coating machine based on Flexible Spring Press (FLEXIS) technology to enhance productivity at CV Cahya Interior Decoration (CID). The main issue faced by the company is the low efficiency of manual HPL coating, which requires 40 minutes per product and results in an average of 15 defective units per month. This inefficiency leads to a financial loss of Rp 1.3 million per month and reduces the company's competitiveness in meeting market demand. As a solution, the FLEXIS machine was developed using a roll press system integrated with a spring flexible mechanism, allowing for more stable automatic pressure during the coating process. The machine is designed with a hollow steel frame and equipped with bearings, a 0.5 HP electric motor, and a gearbox to ensure optimal performance. The fabrication process considers aspects of energy efficiency, ease of maintenance, and material durability. The implementation results demonstrate a significant improvement in production efficiency. The coating time per product was drastically reduced from 40 minutes to 6 minutes, the daily production capacity increased from 3 to 4 units, and the defect rate was successfully reduced to zero units. The economic impact includes a 55.9% increase in CID’s monthly revenue, from Rp 156,000,000 to Rp 204,500,000, contributing to the company’s sustainable business growth.